Summer longing [large type] - Brenner, Jamie, 1971- (Thorndike Press, 2021)
Ruth Cooperman arrives in beautiful beachside Provincetown for her retirement, renting the perfect waterfront cottage while she searches for her forever home. After years of hard work and making peace with life's disappointments, Ruth is looking forward to a carefree summer of solitude. But when she finds a baby girl abandoned on her doorstep, Ruth turns to her new neighbors for help and is drawn into the drama of the close-knit community. The appearance of the mystery baby has an emotional ripple effect through the women in town, including Amelia Cabral, the matriarch who lost her own child decades earlier; Elise Douglas, owner of the tea shop who gave up her dream of becoming a mother; and teenage local Jaci Barros who feels trapped by her parents' expectations. Ruth, caring for a baby for the first time in thirty years, finally reaches out to her own estranged daughter, Olivia, summoning her to Provincetown in hopes of a reconciliation. As summer unfolds and friends and family care for the infant, alliances are made, relationships are tested, and secrets are uncovered. But the unconditional love for a child in need just might bring Ruth and the women of Provincetown exactly what they have been longing for themselves."--Provided by publisher.